(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Development is a very important facet of this world, which is important for the societal well-being. But these developments shouldn’t exert much pressure on the resources which might deteriorate the environment. The environmental, social and economic wellness is that the need of the hour, which amalgamates together within the concept of sustainable development. Solving these environmental problems and preventing new ones would force an understanding and appreciation of the linkages between environmental well-being and human well-being. However, many of those linkages don’t seem to be apparent. To bring environment and development concerns to people’s notice, to enable them to know the linkages between the 2, to encourage them to require appropriate action, and to equip them with the abilities necessary for taking the specified action, education is important for all this. The awareness of those prevailing dangerous situations of earth has led many scientists and eminent persons to predict about what could happen to the planet if it goes the identical way. This can be how the concept of protection and conservation of earth came into existence. Various measures were planned and adopted to some extent, though not successfully to manage the environmental devastation at the international level. So as to evoke awareness and to keep up the balance of the ecosystem, Education (Specially the Higher Education) is very important. The present research work is a contribution to the development of Higher education and its impact on Development of the country. The researcher has made efforts to collect the relevant analysis for finding out the chemistry between Higher Education and development.